2020
DOI: 10.1111/tpj.15031
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome reciprocal translocations have accompanied subspecies evolution in bananas

Abstract: Chromosome rearrangements and the way that they impact genetic differentiation and speciation have long raised questions from evolutionary biologists. They are also a major concern for breeders because of their bearing on chromosome recombination. Banana is a major crop that derives from inter(sub)specific hybridizations between various once geographically isolated Musa species and subspecies. We sequenced 155 accessions, including banana cultivars and representatives of Musa diversity, and genotyped-by-sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(72 citation statements)
references
References 63 publications
5
67
0
Order By: Relevance
“…However, the complex breeding history of bananas may further complicate efforts to identify accessions and trace their origins. For example, extensive studies showed frequent occurrences of chromosomal recombination (e.g., reciprocal translocation or chromosomal inversion) in bananas (Baurens et al, 2018 ; Martin et al, 2020a , b ; Cenci et al, 2021 ). These genome structural diversities have been applied to study the origins of banana cultivars and Musa evolution (Martin et al, 2020b ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the complex breeding history of bananas may further complicate efforts to identify accessions and trace their origins. For example, extensive studies showed frequent occurrences of chromosomal recombination (e.g., reciprocal translocation or chromosomal inversion) in bananas (Baurens et al, 2018 ; Martin et al, 2020a , b ; Cenci et al, 2021 ). These genome structural diversities have been applied to study the origins of banana cultivars and Musa evolution (Martin et al, 2020b ).…”
Section: Introductionmentioning
confidence: 99%
“…In the recent studies that used the sequencing database of M. acuminata ssp. malaccensis reverence chromosomes [26] and chromosome painting [43], a translocation event between chromosomes 1 and 4 was present in ssp. malaccensis.…”
Section: Discussionmentioning
confidence: 99%
“…The range of M. acuminata spans from India at the west to north Australia at the east. It is divided into several subspecies that are geographically segregated and show unique features, morphologically (Simmonds 1956), genetically (Hippolyte et al 2012) and at the genome level (Martin, Baurens, et al 2020). The AA bananas were first hypothesized originating in Malaysia (Simmonds and Shepherd 1955) but molecular studies comparing edible AAs with different M. acuminata subspecies later pointed at the Philippines -New Guinea (NG) region as the centre of origin for the crop (Carreel et al 2002).…”
Section: Introductionmentioning
confidence: 99%